FSM based digital design using verilog HDL - Minns, Peter D. (J. Wiley & Sons, 2008)
FSM based Digital Design with Verilog HDL covers the design and use of finite state machines (FSMs) in digital systems, including stand-alone applications, as well as systems that use microprocessors, micro-controllers, memory controlled directly from the FSM, as well as other common situations found in practical digital systems. The emphasis is on obtaining a good understanding of FSMs, how they can be used, and where to use them. The authors set out a number of practical applications and worked through problems, and there is also an accompanying CD containing software tools for the capture, simulation and implementation of design solutions, with detailed instructions on how to use a particular tool.